Deformation of a Nonhomogeneous Visco-Elastic Hollow Sphere - El-Karamany, A. M. (Engineering Transactions, 1983)
Symmetric deformation of a non-homogeneous visco-elastic hollow sphere subjected to internal and external pressures is investigated. The problem is solved by the elastic-viscoelastic analogy. An exact solution is obtained. A numerical example is given. The nonhomogeneity is shown to decrease he maximum stresses.